(untitled) (Clinics, 2012)
Patients who have suffered burns frequently experience psychological consequences, among which anxiety disorders are prominent. Benzodiazepines are commonly administered to treat these symptoms. The effects of benzodiazepines on healing may not be direct but rather are modulated by alterations of the sleep architecture. This hypothesis is supported by studies that demonstrate the effects of benzodiazepines on the immune system and the inflammatory profile under both normal sleep conditions and during sleep deprivation, particularly rapid eye movement sleep deprivation.